2021
DOI: 10.3390/jcm10091815
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis and Comparison of Six Serological Assays up to Eight Months Post-COVID-19 Diagnosis

Abstract: Background: There is much data available concerning the initiation of the immune response after SARS-CoV-2 infection, but long-term data are scarce. Methods: We thus longitudinally evaluated and compared the total and neutralizing immune response of 61 patients to SARS-CoV-2 infection up to eight months after diagnosis by RT–PCR using several commercial assays. Results: Among the 208 samples tested, the percentage of seropositivity was comparable between assays up to four months after diagnosis and then tended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
4
6
0
Order By: Relevance
“…A first performance test was conducted with a large number of serum samples from COVID-19 patients collected at different times after the onset of COVID-19 symptoms. The results indicated good correspondence between IgG titers and progression of the immune response, in agreement with reports on other serological tests based on ELISA or automated assays [30,31]. A second performance test conducted at InDRE confirmed that UDITEST-V2G ® has high sensitivity (99.33%) and specificity (97.82%) with no interference from other viral infections.…”
Section: Discussionsupporting
confidence: 86%
“…A first performance test was conducted with a large number of serum samples from COVID-19 patients collected at different times after the onset of COVID-19 symptoms. The results indicated good correspondence between IgG titers and progression of the immune response, in agreement with reports on other serological tests based on ELISA or automated assays [30,31]. A second performance test conducted at InDRE confirmed that UDITEST-V2G ® has high sensitivity (99.33%) and specificity (97.82%) with no interference from other viral infections.…”
Section: Discussionsupporting
confidence: 86%
“…Gillot et al evaluated the CoviDiag ® assay and concluded that the combination of several antigens in the same test improves the overall specificity and sensitivity of the test [ 17 ]. Similarly, in our previous work based on the same set of sample, we have found equivalent to improved diagnostic performances, especially for ancient infections, for the CoViDiag ® multiplex IgG assay compared to other simplex IgG commercial assays [ 13 ]. Is is now generally admitted that antibody levels are weaker for asymptomatic and mild form of the disease and can decrease over time.…”
Section: Discussionsupporting
confidence: 67%
“…The CoViDiag assay algorithm adapts the cut-offs depending on the number of different IgGs detected to deliver SARS-CoV-2 positivity status, and maintain diagnostic sensitivity and specificity performances over time. Those results may explain our previous observations on the same cohort [13], where we have observed that the CoViDiag 1 diagnostic sensitivity performance remained more stable over time than for two other commercial references of simplex IgG immunoassay (Abbot 1 and Euroimmun 1 IgG assays, based on the NP and the S1 antigen, respectively).…”
Section: Plos Onesupporting
confidence: 72%
See 2 more Smart Citations